x^2=y^2-8
(-1)^2=3^2-8
1=9-8
1=1
ответ: является
да х_р тебе в рот личинка
Объяснение:
п_дуй от сюда н_уй это го*но-сайтответ:
да х_р тебе в рот личинка
Объяснение:
п_дуй от сюда н_уй это го*но-сайтответ:
да х_р тебе в рот личинка
Объяснение:
п_дуй от сюда н_уй это го*но-сайтответ:
да х_р тебе в рот личинка
Объяснение:
п_дуй от сюда н_уй это го*но-сайтответ:
да х_р тебе в рот личинка
Объяснение:
п_дуй от сюда н_уй это го*но-сайтответ:
да х_р тебе в рот личинка
Объяснение:
п_дуй от сюда н_уй это го*но-сайтответ:
да х_р тебе в рот личинка
Объяснение:
п_дуй от сюда н_уй это го*но-сайт
Подставляем вместо х число -1, вместоу число 3,
получаем:
0=0
ответ: является